Study of the Effectiveness of Loading Digging Tools for Doosan SL 500 Excavators and Komatsu 300 Excavators Using the Overall Equipment Effectiveness (OEE) Method to Achieve Over Burden Stripping Targets at PT. Hasta Panca Mandiri Utama Job Site Cita Mine - Bimo Elang Putra; Dedi Yulhendra (Journals Mining Engineering : Bina Tambang, 2024)
PT. Hasta Panca Mandiri Utama Job Site Cita Mineral Investindo is a private company engaged in mining services. PT HPMU has a production target for Overburden stripping of 100,000 bcm, while the actual production amount in the field using the Overall Equipment Effectiveness (OEE) method on the Dossan SL 500 Excavator and Komatsu 300 Excavator is only 89,483 bcm or 75% of the production target in February and amounted to 88,708 bcm or 74.8% of the production target in March. It can be concluded that production during Overburden stripping in the WP 79 area in February and March 2023 has not reached the production target that the company had planned After carrying out the analysis and improvement efforts, the total Overburden stripping production obtained using the Overall Equipment Effectiveness (OEE) method was 229,216 bcm in February and 253,657 in March, this means that the production target has been reached which has been set at 200,000 bcm/month. with the OEE values on the loading and unloading equipment respectively of 67% and 80% in February and 75% and 73% in March, however this OEE value is still far below the world class OEE value standard of 85%.